A comment on dielectric hole burning - Wagner, Achim; Kliem, Herbert (The journal of chemical physics, 1999)
The method of dielectric hole burning is used to distinguish a homogeneous broadened spectrum from a distribution of relaxation times in a dielectric material. After stimulation with a sinusoidal high electric field a time-dependent shift of the response function Φ(t) is observed. This shift is considered to be induced by a frequency selective absorption of energy and an increase of a local fictive temperature. A computer simulation, which is based upon the model of asymmetric double-well potentials for dipole orientations, also shows a time-dependent shift of the response function after applying and removing a sinusoidal high electric field. This behavior is explained considering the time-dependent polarization only. It is shown in this article that it is not necessary to assume an increase of a local fictive temperature caused by a frequency selective absorption of energy.
Gesehen am 15.01.2020